POTENSI TINDAK PIDANA KORUPSI DALAM PENGELOLAAN DANANTARA (ANALISIS PERSPEKTIF SISTEM HUKUM) - Endik Wahyudi; Bagus Marta Yulian (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
The establishment of the Daya Anagata Nusantara Investment Management Agency (Danantara) through Law No. 1 of 2025 represents a strategic initiative by the government to integrate state assets and strengthen the national economic structure in pursuit of Golden Indonesia 2045. With direct presidential authority and initial capital of at least IDR 1,000 trillion, Danantara holds a strong and independent institutional position. However, this institutional design raises serious concerns, particularly regarding the oversight system in fund and budget management. Given the inherent and sometimes unpredictable risks of investment activities, questions arise as to how Danantara implements its programs within the framework of the latest State-Owned Enterprises (BUMN) law and what potential corruption risks may emerge. This study employs a normative juridical method using Lawrence M. Friedman’s legal system theory and Syed Hussein Alatas’s theory of corruption to analyze Danantara’s supervisory structure and legal accountability. It further examines the legal protection provisions within Danantara’s framework, the role of individuals involved, and the mechanisms of public accountability. The findings are expected to contribute to the development of a more comprehensive oversight system for state asset management and to reinforce anti-corruption principles in public investment institutions.